Brain morphological abnormalities in children with cyclin-dependent kinase-like 5 deficiency disorder. (March 2021) - Tang, Yingying; Wang, Zhong Irene; Sarwar, Shaheera; Choi, Joon Yul; Wang, Shan; Zhang, Xiaoming; Parikh, Sumit; Moosa, Ahsan N.; Pestana-Knight, Elia
Abstract: Background: To quantitatively evaluate the brain MRI morphological abnormalities in patients with cyclin-dependent kinase-like 5 deficiency disorder (CDD) on a group level and longitudinally. Methods: We performed surface-based MRI analysis on high-resolution T1-weighted images on three CDD patients scanned at age of three years, and compared with 12 age- and gender-matched healthy controls. We further examined the longitudinal morphological changes in one patient with a follow-up of 5 years. Results: CDD patients presented significant reductions in total intracranial volume, total gray matter (GM) volume and subcortical GM volume compared to controls. For subcortical regions, significant GM volume reductions were seen in the brain stem, bilateral thalamus, bilateral hippocampus, bilateral cerebellum and left amygdala. Although GM volume of cortical mantle did not show statistical differences overall, significant reduction was detected in bilateral parietal, left occipital and right temporal lobes. Cortical thickness exhibited significant decreases in bilateral occipital, parietal and temporal lobes, while surface area did not show any significant differences. Longitudinal follow-up in one patient revealed a monotonic downward trend of relative volume in the majority of brain regions. The relative surface area appeared to gain age-related growth, whereas the relative cortical thickness exhibited a striking progressive decline over time. Conclusions: Quantitative morphology analysis in children with CDD showed global volume loss in the cortex and more notably in the subcortical gray matter, with a progressive trend along with the disease course. Cortical thickness is a more sensitive measure to disclose cortical atrophy and disease progression than surface area. Highlights: Quantitative MRI morphological abnormalities were first reported in children with CDD. Children with CDD showed global volume loss in cortex and more notably in subcortical GM. Longitudinal follow-up showed monotonic downward trend of relative GM volume along with disease course. Cortical thickness was more sensitive to disclose GM atrophy and disease progression than surface area.